2003
DOI: 10.1038/sj.bmt.1704070
|View full text |Cite
|
Sign up to set email alerts
|

Graft-versus-tumor effect in a patient with advanced neuroblastoma who received HLA haplo-identical bone marrow transplantation

Abstract: Summary:A 5-year-old boy received CD34-positive HLA haploidentical bone marrow transplantation from his father as treatment for refractory advanced neuroblastoma. He had residual disease in the para-aortic lymph nodes and multiple bones after the transplant. However, all of his residual disease had disappeared completely 3 years later. He developed grade I acute graft-versus-host disease (GVHD) but had no symptoms of chronic GVHD or any other complications. This case demonstrates the possibility of a graft-ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 9 publications
1
57
0
Order By: Relevance
“…2,3 Given a higher rate of TRM with allogeneic hematopoietic SCT and the occurrence of GVHD, autologous is the preferred therapeutic option for those in need of hematopoietic SCT: only 25 allogeneic transplantations were therefore performed for neuroblastoma in Europe in 2006. [4][5][6][7][8][9] However, progress has been made in allogeneic transplantation both from a better understanding of immunogenicity and decreased transplant toxicity. First, it has been shown that the GVT effect of allogeneic transplantation may be enhanced by several therapeutic modalities: rapid immunosuppression withdrawal, donor lymphocyte infusion, 10,11 natural killer (NK) cell alloreactivity, 9,12 minor histocompatiblity Ag targeting.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Given a higher rate of TRM with allogeneic hematopoietic SCT and the occurrence of GVHD, autologous is the preferred therapeutic option for those in need of hematopoietic SCT: only 25 allogeneic transplantations were therefore performed for neuroblastoma in Europe in 2006. [4][5][6][7][8][9] However, progress has been made in allogeneic transplantation both from a better understanding of immunogenicity and decreased transplant toxicity. First, it has been shown that the GVT effect of allogeneic transplantation may be enhanced by several therapeutic modalities: rapid immunosuppression withdrawal, donor lymphocyte infusion, 10,11 natural killer (NK) cell alloreactivity, 9,12 minor histocompatiblity Ag targeting.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there were some clinical reports of a GVT effect against neuroblastoma as follows: minimal residual disease in BM disappeared after the cessation of immunosuppressant 13 or after donor lymphocyte infusion, 14 and abnormal uptake on MIBG imaging disappeared 3 years after haploidentical PBSCT from the patient's father. 12 In our case 1, the urinary HVA level became normal at 3 years after uCBT. During reconstitution of the immune system after CBT, T-cell recovery is very slow, but functional NK cells recover within 1 month, 15,16 suggesting that alloreactive NK cells might have an important role in the GVT effect particularly in the early phase after CBT.…”
Section: Discussionmentioning
confidence: 95%
“…10,11 However, allo-SCT was recently reported to induce a graft-versus-tumor (GVT) effect against advanced neuroblastoma in some cases. [12][13][14] We performed a tandem transplantation consisting of autologous PBSCT (auto-PBSCT) followed by allogeneic cord blood transplantation (CBT) in three consecutive pediatric patients with stage 4 neuroblastoma exhibiting high MYCN amplification. They are alive without disease recurrence for 37-60 months after CBT.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, alloreactive T-cells of the donor can recognize the recipient cells as "foreign" and attack them, resulting in the development of "graft versus host disease" (GvHD) and transplantation related mortality. Interestingly, GvHD is often associated with a graft versus tumor (GvT) effect, in which alloreactive T-cells induce destruction of the tumor cell [57].…”
Section: Immunocytokinesmentioning
confidence: 99%